Path of fire : The patterns of chaos #2 - Ingrid, Charles (U.S.A. : Daw Books, Inc., 1992)
When Palaton linked with the young human male named Ran, it was the beginning of a symbiosis that would see both transformed into a new gestalt identiy, no longer quite a part of either race.
Chapter 1 Chapter 2 Chapter 3 Chapter 4 Chapter 5 Chapter 6 and other twenty one chapters more
Keywords: ENGLISH LITERATURE; STORY